Yîhcamnopura Natu Cetaknamachonhîrî: processos informemorias e identidade cultural dos Waiwai do Anauá em Roraima - Pinheiro, Mariza de Oliveira (2019)
The object of this thesis is Information, Memory and Indigenous Cultural Identity of the Waiwai people, from the North of Brazil, it’s inserted in the investigative line of Information, Memory and Society, and it’s especially related to the following areas: Science of Information, Anthropology, History, Literature and Visual Arts. The purpose is to analyze the influences of our matrix as Brazilians, also to respond how the information about cultural identity, particularly referring to the Waiwai people from the north of Brazil, is present in the collective memory of this culture, considering the influences of the Portuguese colonization. The methodology used is duly substantiated in the Geertz’s (2008; 2014) anthropological and hermeneutic paradigm effort of understanding the complex reality and multiple (ontology) of the Waiwai people and its culture (matrix in anthropology), characterized by it’s subjective and complex sphere. The theoretical contribution has it’s matrix in the Social Sciences for the possibility of diversification of methods and mainly for the support of the Science of Information, having it as a conception of Science, which provides a creative epistemology, that I’ve named as intellectual Ethopoisi. It’s classified as a qualitative investigation. The ethnographic approach is utilized through the practice of participant observation and the field diary, based on Assmann (2011); Halbwachs (2003); Candau (2012); Bauman (2005, 2012, 2013) e Hall (2011) and which will report about the memory categories and cultural identity. There isn’t a rigid hierarchic sequence in the ethopoiesi process of knowledge. Will attempt to “compose” a line of thought, interconnected to a rhizomatous net, where the theoretical and methodological elements make up a harmonic set of investigation in the epistemological moralistic perspective. The cultural memory and indigenous identity highlighted represent a bond between time and memory space. These recollections evoked in the present contribute to the transmission and diffusion of tradition. The information flow that’s transmitted “protects” the past from being forgotten and contributes with the knowledge sharing between eras and generations. The Waiwai’s complex process of identity aggregation also involves metaphysical questions. It’s the result of the dialectical inflection between “oneself” and the Other which are presented by Ricoeur (2014). The “oneself” transmutates as the Other in a collective way when it’s created in one of the members of another group-community (Waiwai Anauá). The cultural identity ethnonym of the Waiwai people in the Anauá community was characterized by a complex and fragmented construction that passes as “translated” notion and interpretative in the ethnohistoric registers. The deodontologic moralistic conception (which every ancient value of every ethnicity is aggregated) furthermore it continues vinculated to the ethical teleological conception of the Waiwai community (cosmology of the ethnic origin + christian values of MEVA). Thus way the “oneself” is not just “me” (individuality of the oneself), it can also be considered as “others”, therefore the symbolic representation of the cultural values rooted in the ethnic memory of the collective ethnic of one’s heritage (ancestors). Furthermore, it’s a fact that the symbolic heritage that’s representated by costumes, values and practices of the Waiwai women, materializes through mnemonic supports that these symbolic heritages represented by the costumes, values and practices that work as triggers. The ethno information flow that is transmitted “protects” the past from being forgotten and contributes to the knowledge shared between generations and eras. The contact with religious missions favored a natural transmutation between the traditional native culture and the religious manifestations, which generated significant transformations in the cultural identity of the Waiwai people.